Thermoresponsive Reversible Unimer Micelles of Amphiphilic Fluorinated Copolymers. Issue 3 (4th December 2022) - Guazzelli, Elisa; Masotti, Elena; Kriechbaum, Manfred; Uhlig, Frank; Galli, Giancarlo; Martinelli, Elisa
Abstract: Amphiphilic fluorinated copolymers PEGMA x ‐ co ‐FA y and TEGMA x ‐ co ‐FA y are prepared by activators regenerated by electron transfer atom transfer radical polymerization (ARGET‐ATRP). All polymers present a reversible thermoresponsive lower critical solution temperature‐type behavior, and a cloud point temperature ( T c ) in the range of 30–60 °C strictly dependent on the length of the oxyethylene side chain, the content of the hydrophobic counits, and the concentration of the solution. Combined small angle X‐ray scattering (SAXS) and dynamic light scattering measurements are used to study the self‐assembly behavior in water, organic solvents (tetrahydrofuran [THF] and dimethylformamide [DMF]), and a fluorinated solvent (hexafluorobenzene [HFB]). SAXS confirms the formation of compact‐globular single‐chain self‐folded unimer micelles in water below T c, which generally presents small hydrodynamic diameters ( D h ≤ 8 nm) as a result of the folding of the hydrophobic perfluorohexylethyl acrylate counits. The copolymers are also able to form reverse unimer micelle in HFB. The copolymers are not able to self‐assemble in unimer micelles in THF or DMF solutions, in which they adopt conventional random coil conformations. Abstract : Dynamic light scattering and small angle X‐ray scattering elucidate the morphology and size of self‐folded unimer micelles of oligoethyleneglycol methyl ether methacrylate‐co‐perfluorohexylethyl acrylate. Compact folded unimers are observed in water. Tetrahydrofuran and dimethylformamide organic solutions show a random coil conformation emphasizing the role of a selective solvent to trigger intramolecular self‐folding. Similarly,  hexafluorobenzene produces reverse unimer micelles through solvophobic interactions.